1997
DOI: 10.1128/jb.179.10.3365-3367.1997
|View full text |Cite
|
Sign up to set email alerts
|

Antimonite is accumulated by the glycerol facilitator GlpF in Escherichia coli

Abstract: In a search for genes responsible for the accumulation of antimonite in Escherichia coli, TnphoA was used to create a pool of random insertional mutants, from which one antimonite-resistant mutant was isolated. Sequence analysis showed that the TnphoA insertion was located in the glpF gene, coding for the glycerol facilitator GlpF. The mutant was shown to be defective in polyol transport by GlpF. These results suggest that in solution Sb(III) is recognized as a polyol by the glycerol facilitator.Resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(140 citation statements)
references
References 15 publications
3
137
0
Order By: Relevance
“…Through the regulation of this uptake, the channel has been suggested to have a role in toxic metalloid resistance in yeast (36). In the same study, no equivalent uptake could be demonstrated for GlpF, although GlpF has already been suggested to transport Sb(III), but not As (III), in E. coli (16), thus indicating a specificity difference between these close homologs. This hypothesis awaits a more thorough functional analysis of the transport specificity of Fps1p, which is currently in progress.…”
Section: Discussionmentioning
confidence: 74%
“…Through the regulation of this uptake, the channel has been suggested to have a role in toxic metalloid resistance in yeast (36). In the same study, no equivalent uptake could be demonstrated for GlpF, although GlpF has already been suggested to transport Sb(III), but not As (III), in E. coli (16), thus indicating a specificity difference between these close homologs. This hypothesis awaits a more thorough functional analysis of the transport specificity of Fps1p, which is currently in progress.…”
Section: Discussionmentioning
confidence: 74%
“…Aquaglyceroporins have been shown to facilitate metalloid uptake in both E. coli (13) and S. cerevisiae (18). Without these transporters, cells are unusually resistant to arsenite and͞or antimonite.…”
Section: Discussionmentioning
confidence: 99%
“…Two microbial aquaglyceroporins have been shown to facilitate metalloid uptake, GlpF in E. coli (13) and Fps1p in S. cerevisiae (18). The most closely related mammalian homologs to the two microbial proteins are AQP7 and AQP9.…”
Section: Aqp9 Complements the Metalloid Resistance Phenotype Of An Fps1⌬mentioning
confidence: 99%
See 2 more Smart Citations